Asthma From Childhood Asthma to ACOS Phenotypes - Pereira, Celso (IntechOpen, 2016)
The clinical specificities developed in this book, particularly from those reported in the pediatric population to those reported in complex shapes at ACOS patients, emphasize the importance of identifying not only biomarkers but also critical aspects regarding the variability in pharmacogenomics responsible for the individual response to the different drugs on the therapeutic plan. The contribution of several well-known specialists with their profound knowledge inherent to this issue into different age groups and socio geographical contexts has resulted in this interesting book with relevant key contents in asthma.